Aplicación del material concreto no estructurado en el aprendizaje de la adición y sustracción en los niños/as del 2do grado de primaria de la I.E José Carlos Mariátegui - Valle Arce, David (2011)
This research wor'k was the implementation of concrete material in the process unstructured learning of addition and subtraction, for which we worked with a sample of 9 girls and 8 boys in the second grade of primary leve! of tE "José Carlos Mariategui" located in the district of Rioja. The problem arase because of the experience gained during the development of our professional practicas, where there were certain deficiencias in learning the basic operations of addition and subtraction. In this sense, it was proposed to apply the use of concrete materials unstructured in the prospect of using these materials; children improve their learning of addition and subtraction operations, which constituted the overall objective of this research. Regarding operations, the children considerad in the sample were initially evaluated to see what state they enterad the experiment, which was contrastad with the implementation of post-test. Presumably, these latter results would be better for the start, because the children were stimulated with concrete materials such as unstructured yupana, the positional and the balance board to add. This basic assumption was the research hypothesis, whose contrast was performed by student t test for paired difference. In terms of results, to test the hypothesis test worked with a confidence level of 95%, concluding that the application of concrete materials unstructured children significantly improved their learning operations addition and subtraction, both conceptual and procedural dimensions. They also showed improved altitudes toward the study, motivated by the materials used in each training session.